Iron overload threatens the growth of osteoblast cells via inhibiting the PI3K/AKT/FOXO3a/DUSP14 signaling pathway. Issue 9 (29th January 2019) - Xia, Demeng; Wu, Jianghong; Xing, Malcolm; Wang, Yang; Zhang, Hongyue; Xia, Yan; Zhou, Panyu; Xu, Shuogui
Abstract: Iron overload is a common stress in the development of cells. Growing evidence has indicated that iron overload is associated with osteoporosis. Therefore, enhancing the understanding of iron overload would benefit the development of novel approaches to the treatment of osteoporosis. The purpose of the present study was to analyze the effect of iron overload on osteoblast cells, via the MC3T3‐E1 cell line, and to explore its possible underlying molecular mechanisms. Ferric ammonium citrate (FAC) was utilized to simulate iron overload conditions in vitro. FAC‐induced iron overload strongly suppressed proliferation of osteoblast cells and induced apoptosis. Moreover, iron overload strongly suppressed the expression of dual‐specificity phosphatase 14 (DUSP14). Additionally, overexpression of DUSP14 protected osteoblast cells from the deleterious effects of iron overload, and this protective effect was mediated by FOXO3a. Additionally, matrine rescued the function of DUSP14 in osteoblast cells. Most importantly, our analysis demonstrated the essential role of the PI3K/AKT/FOXO3a/DUSP14 signaling pathway in the defense against iron overload in osteoblast cells. Overall, our results not only elucidate deleterious effects of iron overload, but also unveil its possible signaling pathway in osteoblast cells. Abstract : Our results demonstrated that iron overload deeply suppressed the growth of osteoblast cell. Moreover, the level of dual‐specificity phosphatase 14 (DUSP14) was negatively correlated with the concentration of iron, which was mediated by FOXO3a in MC3T3‐E1 cells. The PI3K/AKT/FOXO3a/DUSP14 might be a novel signaling pathway for the cell defense under iron overload stress.